PENGARUH PEMBERIAN GULA PASIR DAN PUPUK GAVIOTA MENGGUNAKAN TEKNIK PERENDAMAN TANAMAN ANGGREK BULAN (Phalaenopsis hibrida) PADA FASE PEMBIBITAN: Kata kunci: Anggrek Bulan, Pupuk Gaviota, Gula Pasir - wahyu agustina agustina; Dewi Ratna Nuhayati; Sumarmi Sumarmi (Innofarm:Jurnal Inovasi Pertanian, 2023)
The research entitled Effect of Giving sugar and Gaviota Fertilizer Using Soaking Techique on Moon Orchids (Phalaenopsis Hiybrid) in Nursery Phase will be held on 17 Oktober 2022 to 9 January 2023 at the Green Leaves Orcid Garden in Sinoman Tempel Village, District Sidorejo, Salatiga. The purpose of this study was to determine the effect of giving Sugar and Gaviota Fertilizer at certain doses on the growth of the moon orchids in the nursery phase. Research using Gaviota fertilizer (P) with 3 level, without treatment 0 g/liter (P0), 15 g/liter) and 25 g/liter (P2), the second factor was Sugar (S) with 3 levels, namely without treatment 0 g/liter (S0), 2.5 g/liter (S1), 3.5 g/liter (S2). Parameters observed included the number of roots, root length (cm), number of new leaves, leaf length (cm), leaf width (cm), growth percentage. Both treatments provide response or effect on the treatment of Gaviota fertilizer and Sugar doses.